Estudo do efeito de naftopiranonas de espécies de paepalanthus sp sobre Helicobacter pylori, macrófagos ativados e linhagem celular de adenocarcinoma gástrico - Ardisson, Juliana Santa (2018)
The naphthopyranones paepalantine and 5-methoxy-3,4-dehydroxanthomegnin were isolated from Paepalanthus sp and showed antioxidant, anti-inflammatory, antitumor and antimicrobial potential, including anti-H. pylori. H. pylori infection is one of the main causes of gastric cancer. The infection causes an excessive inflammatory response through the neutrophils and macrophages infiltration, increasing the release of reactive species and inducing the production of pro-inflammatory mediators. In the gastric environment, H. pylori expresses the urease enzyme, increasing the pH of the medium through ammonia production. In this context, our aim was to evaluate the activity of naphthopyranones in H. pylori, immunomodulation in macrophages and cytotoxic action in gastric adenocarcinoma cell line and to confirm the potential of interaction of these substances in the urease and iNOS binding sites through molecular docking studies. The determination of the minimum inhibitory concentration (MIC) of the naphthopyranones for H. pylori was performed by broth microdilution technique for further analysis of the synergistic activity with metronidazole and for morphological analysis by scanning electron microscopy (SEM). The evaluation of the urease inhibition by the naphthopyranones was performed in vitro and in silico. The immunomodulatory activity of naphthopyranones was evaluated detecting the nitric oxide and cytokines (TNF-α, IL-1β, and IL-6) released by macrophages, and the interaction potential of the naphthopyranones within iNOS binding site was studied in silico. The reduction of the pathogenicity of H. pylori in macrophages was investigated after treatment with sub-inhibitory concentrations of the naphthopyranones. Finally, cytotoxic activity in gastric adenocarcinoma cells (AGS) was evaluated by the MTT assay. 5-methoxy-3,4-dehydroxanthomegnin is shown to inhibit H. pylori (metronidazole resistant strain) synergistically with metronidazole, reducing its MIC to 8 μg/mL. The results of the scanning electron microscopy, that evaluated the H. pylori morphology, evidenced that the naphthopyrananones alter the H. pylori morphology, indicating a possible role on the Penicilin-binding protein (PBPs) due to the bacterial cell wall modifications. It was also verified that H. pylori grow under naphthopyranones sub-inhibitory concentrations causes reduction of the activation of macrophages by inhibition of NO production in 60.21 ± 1.8% for paepalantine and 47.50 ± 0.6% for 5- methoxy-3,4-dehydroxanthomegnin. Regarding urease inhibition, no significant inhibitory activity of the samples and no favorable interactions with the major aminoacid residues in the active site of this enzyme was observed. The samples demonstrated immunomodulatory potential by inhibiting the proinflammatory cytokines produced by LPS stimulated macrophages (TNF-ɑ inhibition of 36.07 ± 2.63% and 60.19 ± 0.12% and IL-6 inhibition of 36.91 ± 0.57% and 92.35 ± 0.15% of paepalantine and 5-methoxy-3,4-dehydroxanthomegnin respectively, both at 25 μg/mL) and NO (99.5 ± 5.31% for paepalantine and 76.9 ± 4.11% for 5-methoxy-3,4- dehydroxanthomegnin at a concentration of 12.5 μg/mL) and also demonstrated interaction potential in the active site of the iNOS enzyme. In addition, naphthopyranones demonstrated satisfactory cytotoxic activity in AGS, with IC50 of 24.56 ± 2.3 μg/mL for paepalantine and 17.45 ± 1.6 μg/mL for 5-methoxy-3,4- dehydroxanthomegnin. In general, the naphthopyranones demonstrate potential for future use in the treatment and prevention of H. pylori infection as well as the diseases related to this infection, especially gastric cancer.